Scoping review of the characteristics assessed by vulnerability indices applied to people experiencing homelessness. - Jane Currie; Elizabeth Grech; Erin Longbottom; Jasmine Yee; Ruth Hastings; Amy Aitkenhead; Amy Cason; Karin Obrecht (PLoS ONE)
Background The objectives of this scoping review are to investigate the characteristics assessed by existing vulnerability indices and the health outcomes achieved by applying them to people experiencing homelessness. This review forms part of the development and implementation of a novel tool to prioritise people experiencing homelessness for healthcare based on their need and capacity to access healthcare. Methods Included papers were primary research, published in the English language, participants were experiencing homelessness and aged over 18 years at the time of the study, a vulnerability index was used in the study, sample size was greater than 30, and the study had a health focus. Databases searched were MEDLINE, Embase, CINAHL, Scopus, PubMed and Web of Science, between January-April 2020. The Joanna Briggs Appraisal criteria were used to quality appraise the included studies. Results were synthesised narratively. Results Six papers were included, a total of 27,509 participants. The reported use of the indices varied; they included screening and profiling homeless populations, comparing homeless populations, and two studies evaluated the predictive capacity, reliability and validity of the indices. One vulnerability index focused on screening for human immunodeficiency virus, one used a 50-item index and four used a nine-item index. No direct health outcomes were reported from applying the vulnerability indices. The studies identified limitations of using vulnerability indices, including the potential bias of relying on self-reported data and two studies highlighted the need for further psychometric testing to ensure validity and reliability of the indices. Discussion The sample of included studies was small. Vulnerability indices are reportedly a useful and easily accessible method of gaining valuable data on the health status and health needs of people experiencing homelessness. The variety of characteristics included in the vulnerability indices suggests the importance of tailoring vulnerability indices to the needs of the population to which it is to be applied. Conducting appropriate psychometric testing is critical so that an index can be used to accurately inform decision making and accurately prioritise people experiencing homelessness who are most at risk of mortality and morbidity. A specific tool that prioritises people experiencing homelessness for access to health care is not yet available. The review was funded by a St Vincent's Network Inclusive Health grant.